Reflexiones sobre el análisis de las políticas externas latinoamericanas - Ferguson, Yale H. (Estudios Internacionales, 1986)
A few months ago, those interested in international relations in Latin America witnessed the almost simultaneous appearance of two collections of essays on Latin American foreign policies: Jennie K. Lincoln and Elizabeth G. The Dynamics of Latin American Foreign Policies; and Heraldo Muñoz and Joseph S. Tulchin (editors), Latin American Nations in World Politics. This work is an essay review of both volumes. It is not intended to assess the quality of each of the trials; but rather to use both compilations as a starting point to reflect on the usefulness of various theoretical approaches and concepts, common to the study of general international relations and foreign policy, when it comes to applying them to Latin America.